Metabolomics Signature and Potential Application of Serum Polyunsaturated Fatty Acids Metabolism in Patients With Vitiligo - Ye, Zhubiao; Chen, Jianru; Du, Pengran; Ni, Qingrong; Li, Baizhang; Zhang, Zhe; Wang, Qi; Cui, Tingting; Yi, Xiuli; Li, Chunying; Li, Shuli (Frontiers in Immunology, 2022)
Vitiligo is a depigmented skin disorder caused by a variety of factors, including autoimmune, metabolic disturbance or their combined effect, etc. Non-targeted metabolomic analyses have denoted that dysregulated fatty acids metabolic pathways are involved in the pathogenesis of vitiligo. However, the exact category of fatty acids that participate in vitiligo development and how they functionally affect CD8+ T cells remain undefined. We aimed to determine the difference in specific fatty acids among vitiligo patients and healthy individuals and to investigate their association with clinical features in patients with vitiligo. Serum levels of fatty acids in 48 vitiligo patients and 28 healthy individuals were quantified by performing ultra-performance liquid chromatography-tandem mass spectrometry. Univariate and multivariate analyses were carried out to evaluate the significance of differences. Moreover, flow cytometry was used to explore the effect of indicated fatty acids on the function of CD8+ T cells derived from patients with vitiligo. We demonstrated that serological level of alpha-linolenic acid (ALA) was markedly upregulated, while that of arachidonic acid (ARA), arachidic acid (AA) and behenic acid were significantly downregulated in patients with vitiligo. Moreover, ALA levels were positively associated with vitiligo area scoring index (VASI) and ARA was a probable biomarker for vitiligo. We also revealed that supplementation with ARA or nordihydroguaiaretic acid (NDGA) could suppress the function of CD8+ T cells. Our results showed that vitiligo serum has disorder-specific phenotype profiles of fatty acids described by dysregulated metabolism of polyunsaturated fatty acids. Supplementation with ARA or NDGA might promote vitiligo treatment. These findings provide novel insights into vitiligo pathogenesis that might add to therapeutic options.